Pengukuran Tingkat Kecukupan Sumber Daya Manusia (SDM), Sarana Bantu dan Prasarana Pemanduan Kapal di KSOP Kelas III Tanjung Pakis - Fahmi Hidayatul ‘Ilmi; Rizqi Aini Rakhman; Teguh Pribadi; Indah Ayu Johanda Putri (Pusat Riset dan Inovasi Nasional, 2025)
KSOP Class III Tanjung has a big responsibility in ensuring that the guidance service runs smoothly. However, the realization of the availability of guided facilities and infrastructure is still not in accordance with the state of the field. This study aims to calculate the adequacy level (ideal) of human resources, facilities and infrastructure for ship guidance according to the report of guiding activities. This research is quantitative descriptive with a formula method or an empirical calculation formula of the level of adequacy, used as a reference or reference provided by the Directorate General of Ports. The results of the study show that there is an excess of Human Resources (HR) and Guidance Infrastructure amounting to 2 guides and 1 kepil ship. The factor that affects the calculation of the ideal result is the characteristics of the vessel's guiding area.